Conducting a seminar class "Fundamentals of Traditional Pulse Diagnosis" on the reflexology cycle for students of specialty 227 "Therapy and Rehabilitation" - Chupryna, Gennadii; Gusev, Taras; Martseniuk, Igor; Sibiryakin, Yaroslav; Svyrydova, Nataliа; Sereda, Vitaly (My University, 2023)
This article is devoted to the methodology of conducting a seminar class “Fundamentals of traditional diagnosis by pulse” of the educational discipline of reflexology for students in the specialty 227 “Therapy and rehabilitation”. It provides theoretical data of traditional Chinese medicine, on which pulse diagnosis is based. The following aspects of traditional pulse diagnostics are analyzed: pulse position diagnostics, pulse properties diagnostics. Ця стаття присвячена методиці проведення семінарського заняття «Основи традиційної пульсової діагностики» з навчальної дисципліни рефлексотерапія для студентів спеціальності 227 «Терапія та реабілітація». У ній наведено теоретичні дані традиційної китайської медицини, на яких базується пульсова діагностика. Аналізуються такі аспекти традиційної пульсової діагностики: діагностика положення пульсу, діагностика властивостей пульсу.
Keywords: rehabilitation; реабілітація; reflexotherapy; рефлексотерапія